Adaptation to transboundary climate risks in trade: Investigating actors and strategies for an emerging challenge. (31st January 2022) - Bednar‐Friedl, Birgit; Knittel, Nina; Raich, Joachim; Adams, Kevin M.
Abstract: There is growing recognition that international trade can transmit climate risks across borders, requiring new forms of and approaches to adaptation. This advanced review synthesizes knowledge on how, by whom and where adaptation actions can be taken in the agriculture and industrial sectors to reduce these transboundary climate risks (TCRs). We find a material difference in the literature on TCRs in agriculture as compared with industrial sectors. Operational and market risks, in particular reductions in food availability, dominate in agriculture, while supply chain and trade‐related risks are highlighted for industry. While the origin of the risk (source) is the primary target of adaptation to agricultural TCRs, the general governance structure, such as UNFCCC and WTO deliberations, are important targets in both sectors. Adaptation at the country of destination and along the trade network is of minor importance in both sectors. Regarding the type of adaptation option, agriculture heavily relies on trade policy, agricultural adaptation, and adaptation planning and coordination, while in industry knowledge creation, research and development, and risk management are seen as essential. Governments and the international community are identified as key actors, complemented by businesses and research as critical players in industry. Some measures, such as protectionist trade policies and irrigation, are controversial as they shift risks across countries and sectors, rather than reduce them. While more research is needed, this review shows that a critical mass of evidence on adaptation to TCRs is beginning to emerge, particularly underscoring the importance of international coordination mechanisms. This article is categorized under: Vulnerability and Adaptation to Climate Change > Institutions for Adaptation Vulnerability and Adaptation to Climate Change > Multilevel and Transnational Climate Change Governance Abstract : Agriculture and industry adapting to transboundary climate risks.